Gallery whispers - Jardine, Quintin, 1945- (Headline, 1999)
With his boss recovering from a heart attack, Deputy Chief Constable Bob Skinner is filling his shoes - and that means more time than he'd like sitting behind a desk. But he's about to be provided with more drama than he could ever want.One of the world's most ruthless terrorists is on his way to Edinburgh. -and he can only have one thing on his mind: the forthcoming conference of world Heads of Government. If Skinner doesn't pick up his trail fast, he could have a global disaster in his backyard. While all eyes arc focused on the terrorist threat, a terminally ill woman is found dead -an apparent suicide. But a policewoman sees the subtle marks of an assisted death -and therefore, according to the law, murder. It is the beginning of an ominous pattern. For Skinner, the desperate race to find a heartless terrorist mixes uneasily with the search for a mercy killer - a search which takes on a poignant personal significance. One thing's for sure, Skinner will soon be staring death straight in the eye...